Constructive and technological aspects of the heat flow imitator based on diamond-like films - Nikolaenko, Yu.E.; Melnyk, R.S.; Rudenko, A.I.; Rotner, S.M. (Технология и конструирование в электронной аппаратуре, 2017)
The paper describes features of the design and manufacturing technology of a volumetric detachable heat flow imitator designed for the study of thermal characteristics and for carrying out thermal tests of heat pipes of cooling systems for electronic equipment. The authors use thin alumina ceramic plates with deposited with diamond-like films as heating elements of the imitator. Experimental results are presented on the surface temperature of heating elements and the temperature drop between the heating elements and the heat pipe in the region of the input heat flux values from 5 to 25 W. The use of the proposed heat flow imitator allows speeding up the process of research and testing of heat pipes.